Bantuan Teknik Pembuatan Septik Tank Ferosemen Rumah Tinggal di Kelurahan Labuhan Ratu - Khotimah, Siti Nurul; Alami, Fikri; Martinus (FT Universitas Lampung, 2025)
Bandar Lampung City, Indonesia, still necessitates proper and safe sanitation infrastructure. Particularly, related to blackwater that is stored in the septic tank. A proper and safe septic tank must meet the requirement, preventing leakage and should be designed for periodic emptying. In this community services, the septic tank is designed to be emptied within 3 years. The septic tank infrastructure is designed using ferrocement. The consideration is the technology already common in the usage of water infrastructure as it is strong, leakage resistance, lightweighted and more affordable comparing to concrete. Based on the design, the ferrocement septic tank is designed by two compartment, with 2 meter length, 1 meter width and 1.95 meter in height.